Melanocortin receptor agonist NDP-α-MSH improves cognitive deficits and microgliosis but not amyloidosis in advanced stages of AD progression in 5XFAD and 3xTg mice - Daini, Eleonora; Vandini, Eleonora; Bodria, Martina; Liao, Wenjie; Baraldi, Carlo; Secco, Valentina; Ottani, Alessandra; Zoli, Michele; Giuliani, Daniela; Vilella, Antonietta (Frontiers in Immunology, 2023)
Alzheimer's disease (AD) is the most frequent cause of dementia and still lacks of effective therapy. Clinical signs of AD include low levels of endogenous melanocortins (MCs) and previous studies have shown that treatment with MC analogs induces neuroprotection in the early stages of AD. Here, we investigate the neuroprotective role of MCs in two transgenic mouse models of severe AD using 5 and 7 month-old 5XFAD mice and 9 and 12 mo 3xTg mice. We demonstrated that the chronic stimulation of MC receptors (MCRs) with MC analogue Nle4, D-Phe7α-melanocyte stimulating hormone (NDP-α-MSH, 340 μg/kg, i.p.) improves cognitive abilities of AD mice at late stage of AD progression. We also showed that these protective effects are associated with decreased hyperphosphorylated Tau but not with Aβ burden, that was unaffected in the hippocampus and in the cortex of AD mice. In addition, an age-dependent NDP effect on glial reactivity was observed only in 3xTg mice whereas a global downregulation of p38 mitogen-activated protein kinase was selectively observed in 7 month old 5XFAD and 14 month old 3xTg mice. Our results suggest that MCR stimulation by NDP-α-MSH could represent a promising therapeutic strategy in managing cognitive decline also at late stage of AD, whereas the effects on neuroinflammation may be restricted to specific stages of AD progression.